Closed sampling purge gas adsorption tank and adsorption method
By using a three-dimensional porous polymer matrix and a thermosetting resin-coated oil-absorbing sponge in a closed sampler, efficient adsorption and long-term use are achieved, solving the problems of low adsorption ratio and short replacement cycle of activated carbon adsorption devices, and significantly improving the purge The adsorption effect and safety of gas.
Patent Information
- Application Number
- CN202310728461.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-19
AI Technical Summary
In the existing closed samplers, the activated carbon adsorption device has a low adsorption ratio, a short replacement cycle, and is prone to sticking to the wall, making it difficult to achieve efficient and simple recycling of purge gas, resulting in environmental pollution and human health hazards.
The oil-absorbing sponge including a three-dimensional porous polymer matrix and a thermosetting resin is used as the adsorption material. The super-hydrophobic and super-lipophilic properties of the sponge condense into droplets, and slides down to the liquid collecting chamber through gravity to discharge it regularly to achieve high efficiency. Adsorption and long-term use.
It realizes efficient condensation of condensable gas in the purge gas, with oil and gas adsorption rate greater than 90%, pass rate up to 100%, and has excellent flame retardant characteristics and a wide range of high-temperature applications, ensuring the safety of the petrochemical sampling link.
Smart Images

Figure CN119158372A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of purge gas adsorption, and in particular to a closed sampling purge gas adsorption tank and an adsorption method. Background Art
[0002] In the petrochemical production process, it is often necessary to collect samples of flammable, explosive, or even toxic and harmful gases to monitor the production process and product quality. In order to prevent these gases from leaking into the atmosphere, the collection work must be carried out in a closed sampler. The application of closed samplers effectively prevents the occurrence of dangerous behaviors during the sampling process, prevents occupational disease risks, and protects life and property safety; at the same time, closed samplers reduce the possibility of sample volatilization and contamination, making the test analysis more accurate and reliable. In addition, by cutting off the channel for sample discharge into the atmosphere, it reduces the pollution of the atmospheric environment.
[0003] Before and after sampling, the closed sampler needs to be purged with purge gas to prevent contamination of the sample and gas residue in the pipeline. For the sampling of condensable gases, an adsorption device is generally used to fill the adsorbent for adsorption. Currently, an adsorption device filled with activated carbon is commonly used. However, the activated carbon adsorption device has a low adsorption rate, a short replacement cycle, and is easy to stick to the wall, which limits its application in this field.
[0004] Therefore, a new closed sampler purge gas adsorption device is urgently needed. Summary of the invention
[0005] The purpose of the present invention is to overcome the difficulty that the prior art cannot achieve efficient and simple recovery of the purge gas of a closed sampler, and to provide a closed sampling purge gas adsorption tank. The adsorption tank is used to adsorb the purge gas. The adsorption material has a long replacement cycle and a large adsorption ratio. It can effectively condense the condensable gas in the purge gas to prevent the purge gas from polluting the environment and harming human health.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a closed sampling purge gas adsorption tank, which comprises:
[0007] A tank body and a containing cavity formed around the tank body;
[0008] A support plate is sealed and arranged in the accommodating cavity, wherein the support plate and the tank body form a liquid collecting cavity below the support plate; and the tank body and the support plate form a purge gas adsorption cavity above the support plate; and the support plate is provided with a gas flow channel;
[0009] A sponge disposed on the support plate is used to contact the purge gas and condense the condensable gas in the purge gas into liquid droplets;
[0010] A purge gas inlet pipeline and a purge gas outlet pipeline are provided through the tank body, wherein the port of the purge gas inlet pipeline is provided below the support plate, and the port of the purge gas outlet pipeline is provided above the sponge;
[0011] The sponge includes an oil-absorbing sponge, which includes a three-dimensional porous polymer matrix and a thermosetting resin coated on the three-dimensional porous polymer matrix; the saturated adsorption capacity of the oil-absorbing sponge for oil products is not less than 30g / g; the saturated adsorption capacity of the oil-absorbing sponge for oil products is still not less than 30g / g after 30 adsorption-desorption cycles.
[0012] A second aspect of the present invention provides a closed sampling purge gas adsorption method, the method comprising:
[0013] The purge gas is input into the liquid collecting chamber through the purge gas inlet pipeline. The purge gas contacts the sponge in the purge gas adsorption chamber through the support plate. The condensable gas in the purge gas condenses into droplets, which drop into the liquid collecting chamber under the action of gravity.
[0014] The remaining purge gas is discharged through the purge gas outlet pipeline.
[0015] Through the above technical scheme, the closed sampling purge gas adsorption tank described in the present invention includes the oil-absorbing sponge described in the present invention in the sponge. The oil-absorbing sponge has super-hydrophobic and super-oleophilic properties. The super-oleophilic properties of the oil-absorbing sponge material enable the condensable gas carried in the purge gas to be adsorbed and enriched when it contacts the sponge skeleton, and condense into oil droplets. As the oil droplets gradually grow larger, when the adsorption force of the sponge skeleton on the oil droplets is less than gravity, the oil droplets slide into the liquid collecting cavity, and the oil can be drained regularly.
[0016] In the present invention, the oil-absorbing sponge has a good condensing effect on the condensable gas in the purge gas, the oil and gas adsorption rate is greater than 90%, and the pass rate of the purge gas is 100%; at the same time, the flame retardant grade of the oil-absorbing sponge can reach V-0, and it has very excellent flame retardant properties, providing safety protection for the sampling link of the petrochemical industry, and the oil-absorbing sponge still has a condensing effect on high-temperature oil and gas, and has a wide range of application conditions, achieving unexpected technical effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the structure of a purge gas adsorption tank of a closed sampler provided by a preferred embodiment of the present invention;
[0018] Figure 2 is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Preparation Example 1;
[0019] Figure 3 is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Preparation Example 1 after 30 cycles;
[0020] Figure 4 is a scanning electron microscope (SEM) image of the porous melamine-formaldehyde sponge matrix in Preparation Example 1;
[0021] Figure 5 is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Preparation Example 8;
[0022] Figure 6 This is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Preparation Example 8 after being cycled 30 times.
[0023] Description of Reference Numerals
[0024] 1—tank body 2—pallet
[0025] 3—Sponge 4—Purge gas inlet pipeline
[0026] 5—Purge gas outlet pipeline 6—Drain valve DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] In the present invention, unless otherwise specified, directional words such as "up, down, left, right" generally refer to up, down, left, right as shown in the reference drawings; "inside, outside" refer to inside and outside relative to the outline of each component itself.
[0029] A first aspect of the present invention provides a closed sampling purge gas adsorption tank, the adsorption tank comprising:
[0030] A tank body 1 and a receiving cavity formed around the tank body 1;
[0031] A support plate 2 is sealed and arranged in the accommodating cavity, and a liquid collecting cavity is formed with the tank body 1 below the support plate 2; a purge gas adsorption cavity is formed with the tank body 1 above the support plate 2; and a gas flow channel is arranged on the support plate 2;
[0032] The sponge 3 disposed on the support plate 2 is used to contact with the purge gas and condense the condensable gas in the purge gas into liquid droplets;
[0033] A purge gas inlet pipeline 4 and a purge gas outlet pipeline 5 are provided through the tank body 1, wherein the port of the purge gas inlet pipeline 4 is provided below the support plate 2, and the port of the purge gas outlet pipeline 5 is provided above the sponge 3;
[0034] The sponge 3 includes an oil-absorbing sponge, which includes a three-dimensional porous polymer matrix and a thermosetting resin coated on the three-dimensional porous polymer matrix; the saturated adsorption capacity of the oil-absorbing sponge for oil products is not less than 30g / g; the saturated adsorption capacity of the oil-absorbing sponge for oil products is still not less than 30g / g after 30 cycles of adsorption-desorption. The closed sampling purge gas adsorption tank of the present invention includes the oil-absorbing sponge of the present invention in the sponge 3, and the oil-absorbing sponge has super-hydrophobic and super-oleophilic properties. The super-oleophilic properties of the oil-absorbing sponge material make the condensable gas carried in the purge gas adsorbed and enriched when it contacts the sponge skeleton, and condense into oil droplets. As the oil droplets gradually grow larger, when the adsorption force of the sponge skeleton on the oil droplets is less than gravity, the oil droplets slide into the liquid collection cavity, and the oil can be discharged regularly.
[0035] According to a preferred embodiment of the present invention, a drain valve 6 is further provided at the bottom of the tank body 1 for discharging the collected liquid droplets.
[0036] According to a preferred embodiment of the present invention, the support plate 2 is provided with an opening, and the aperture of the opening is 5-20 mm.
[0037] In the present invention, the sponge is laid on the support plate 2, and the diameter of the sponge is slightly larger than the inner diameter of the tank body, so that the sponge fully fills the accommodating cavity to prevent oil and gas from overflowing; its filling thickness is 1 / 2-2 / 3 of the height of the tank body above the support plate 2. The lower surface of the sponge fits tightly with the support plate. The above filling conditions are all conducive to the full adsorption of the purge gas.
[0038] The oil-absorbing sponge of the present invention has super-hydrophobic and super-oleophilic properties while maintaining the high resilience and high porosity of the original three-dimensional porous polymer matrix. The oil-absorbing sponge has good resilience and strong adsorption capacity for oil products.
[0039] According to a preferred embodiment of the present invention, the mass of the thermosetting resin accounts for 0.5-5%, preferably 2-3%, of the total mass of the sponge.
[0040] According to a preferred embodiment of the present invention, the saturated adsorption capacity of the oil-absorbing sponge for oil is 30-50 g / g.
[0041] The oil-absorbing sponge of the present invention has strong selectivity for oil products in oily wastewater, large adsorption capacity for oil products and can be recycled. The adsorption capacity is basically not attenuated after being recycled for 30 times. According to a preferred embodiment of the present invention, the saturated adsorption capacity of the oil-absorbing sponge for oil products is still 30-50g / g after 30 desorption-adsorption cycles.
[0042] In the present invention, the thermosetting resin can be selected from a wide range, and conventional thermosetting resins in the field can meet the requirements of the present invention. According to a preferred embodiment of the present invention, the thermosetting resin is selected from at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, unsaturated polyester resin and silicone resin; preferably selected from at least one of phenolic resin, epoxy resin and silicone resin.
[0043] In the present invention, the three-dimensional porous polymer matrix only needs to have a through-hole structure inside and a porosity greater than 70%. According to a preferred embodiment of the present invention, the three-dimensional porous polymer matrix is selected from at least one of melamine-formaldehyde sponge, polyurethane sponge and ethylene-vinyl acetate sponge, preferably melamine-formaldehyde sponge.
[0044] In the present invention, the pore size of the oil absorbing sponge can be selected in a wide range. According to a preferred embodiment of the present invention, the pore size of the oil absorbing sponge is 10-500 μm, preferably 100-400 μm.
[0045] In the present invention, the porosity of the oil-absorbing sponge can be selected in a wide range. According to a preferred embodiment of the present invention, the porosity of the oil-absorbing sponge is greater than or equal to 60%, preferably greater than or equal to 90%.
[0046] The oil-absorbing sponge of the present invention has super-hydrophobic and super-oleophilic properties. According to a preferred embodiment of the present invention, the static plane contact angle of the surface of the oil-absorbing sponge to water in air is greater than 135°; preferably greater than 145°.
[0047] The oil-absorbing sponge of the present invention has super-hydrophobic and super-oleophilic properties. According to a preferred embodiment of the present invention, the static contact angle of the surface of the oil-absorbing sponge to white oil is less than 30°; preferably 0-20°; more preferably 0°.
[0048] The oil-absorbing sponge of the present invention also has flame retardant properties; according to a preferred embodiment of the present invention, the UL94 vertical burning test grade of the oil-absorbing sponge is above V-2, preferably above V-1; more preferably V-0.
[0049] The oil-absorbing sponges having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for the preparation method thereof. With respect to the present invention, according to a preferred embodiment of the present invention, the second aspect of the present invention provides a method for preparing the oil-absorbing sponge of the present invention, the method comprising:
[0050] The solution containing the thermosetting resin prepolymer and the curing agent is dispersed into the three-dimensional porous polymer matrix, and cured under vacuum conditions to obtain the oil-absorbing sponge. The preparation method of the present invention disperses (for example, extrusion absorption dispersion, spray absorption dispersion) the solution containing the thermosetting resin prepolymer and the curing agent into the three-dimensional porous polymer matrix and then heats and cures it in vacuum, which can cure the thermosetting resin on the three-dimensional porous polymer matrix while maintaining the high resilience and high porosity of the original three-dimensional porous polymer matrix.
[0051] In the present invention, there is no particular limitation on the dispersion method of dispersing the solution containing thermosetting resin prepolymer and curing agent into the three-dimensional porous polymer matrix, as long as it can be evenly dispersed. According to a preferred embodiment of the present invention, the dispersion method is extrusion absorption dispersion or spray absorption dispersion, preferably extrusion absorption dispersion.
[0052] In the present invention, extrusion absorption dispersion refers to extruding the three-dimensional porous polymer matrix, placing it in a solution containing a thermosetting resin prepolymer and a curing agent, absorbing and restoring it to its original shape, and then extruding it to a certain proportion to discharge the excess solution and disperse it evenly.
[0053] In the present invention, spray absorption dispersion refers to uniformly dispersing a certain amount of thermosetting resin prepolymer and curing agent solution onto the surface of the three-dimensional porous polymer matrix in a spraying manner, waiting for absorption and then heating and curing.
[0054] In the present invention, the curing pressure may be selected in a wide range. According to a preferred embodiment of the present invention, the pressure is 0 to 10 kPa, preferably 3 to 5 kPa.
[0055] In the present invention, the curing conditions have a wide range of optional ranges. According to a preferred embodiment of the present invention, the curing conditions include: a temperature of 80 to 200°C, preferably 100 to 180°C; the curing time can be reasonably adjusted according to actual needs, preferably, the time is 5 to 120 minutes, more preferably 20 to 100 minutes.
[0056] According to a preferred embodiment of the present invention, the method for preparing the oil-absorbing sponge comprises:
[0057] (1) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into a three-dimensional porous polymer matrix, and pre-curing under a first vacuum condition;
[0058] (2) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into the product obtained in step (1), and curing the product under a second vacuum condition;
[0059] The first vacuum condition and the second vacuum condition each include: a pressure of 0-10 kPa;
[0060] Pre-curing conditions include: temperature of 80-120°C;
[0061] Curing conditions include: temperature of 140-180°C.
[0062] In the present invention, the thermosetting resin prepolymer is pre-cured to make the overall temperature of the sponge uniform, the thermosetting resin inside reaches a gel state, and is attached to the three-dimensional porous polymer matrix skeleton. The vacuum condition is conducive to the gas discharge in the thermosetting resin in the gel state, and better combined with the sponge skeleton. Then, the solution containing the thermosetting resin prepolymer and the curing agent is dispersed on the three-dimensional porous polymer matrix containing the gel-state thermosetting resin, and cured to obtain the oil-absorbing sponge, which is conducive to the uniform distribution of the thermosetting resin on the sponge skeleton, thereby maintaining the elasticity of the three-dimensional porous polymer matrix, improving the recyclable performance of the oil-absorbing sponge, and the adsorption capacity is basically not attenuated when it is recycled for 30 times.
[0063] According to a preferred embodiment of the present invention, in step (1), the gel-state thermosetting resin accounts for 0.5-1% of the total mass of the sponge, which is beneficial to further maintain the elasticity of the three-dimensional porous polymer matrix and improve the recycling performance of the oil-absorbing sponge.
[0064] In the present invention, in step (1), there is no special requirement for the pre-curing time, which can be reasonably adjusted according to actual needs, as long as the thermosetting resin prepolymer forms a gel-state thermosetting resin in the three-dimensional porous polymer matrix. According to a preferred embodiment of the present invention, the pre-curing time is 40-90 minutes.
[0065] In the present invention, in step (2), the curing time is 20-100 minutes.
[0066] According to a preferred embodiment of the present invention, in the solution containing the thermosetting resin prepolymer and the curing agent, the mass concentration of the thermosetting resin prepolymer is 0.02 to 0.6 g / mL, preferably 0.03 to 0.5 g / mL, and more preferably 0.05 to 0.3 g / mL.
[0067] According to a preferred embodiment of the present invention, in the solution containing the thermosetting resin prepolymer and the curing agent, the mass of the curing agent accounts for 1 to 10% of the mass of the thermosetting resin prepolymer; preferably 5 to 10%.
[0068] In the present invention, in the solution containing thermosetting resin prepolymer and curing agent, the optional range of solvent is relatively wide, as long as it can dissolve the thermosetting resin prepolymer and the curing agent. According to a preferred embodiment of the present invention, in the solution containing thermosetting resin prepolymer and curing agent, the solvent is selected from at least one of water, C1-C4 alcohol and C1-C4 ketone; preferably ethanol and / or acetone.
[0069] In the present invention, in the solution containing the thermosetting resin prepolymer and the curing agent, the curing agent has a wide range of options, as long as it can form the thermosetting resin with the thermosetting resin prepolymer. According to a preferred embodiment of the present invention, the curing agent is selected from at least one of organic acids, acid anhydrides, boron trifluoride, aliphatic polyamines and aromatic polyamines; preferably at least one of benzenesulfonic acid, hexamethylenetetramine and meta-phenylenediamine.
[0070] A second aspect of the present invention provides a closed sampling purge gas adsorption method, the method comprising:
[0071] The purge gas is input into the liquid collecting chamber through the purge gas inlet pipeline 4. The purge gas contacts the sponge 3 in the purge gas adsorption chamber through the support plate 2. The condensable gas in the purge gas condenses into liquid droplets, which drip into the liquid collecting chamber under the action of gravity.
[0072] The remaining purge gas is discharged through the purge gas outlet pipeline 5. Using the adsorption method of the present invention, the oil absorption sponge has a good condensation effect on the condensable gas in the purge gas, the oil and gas adsorption rate is greater than 90%, and the passing rate of the purge gas is 100%.
[0073] In the present invention, the source and type of the purge gas can be selected in a wide range. According to a preferred embodiment of the present invention, the purge gas comes from a PX device, and contains 0-10% toluene, 0-20% p-xylene, and 70-98% nitrogen by volume.
[0074] In the present invention, the optional range of the purge gas adsorption conditions is relatively wide. According to a preferred embodiment of the present invention, the adsorption conditions include: an adsorption temperature of -20-40°C.
[0075] According to a preferred embodiment of the present invention, the liquid droplets collected in the liquid collecting chamber are discharged through the liquid discharge valve 7 .
[0076] The present invention will be described in detail below through examples.
[0077] In the following embodiments, the structural schematic diagram of the adsorption tank is as follows Figure 1 As shown, the adsorption tank includes:
[0078] A tank body 1 and a receiving cavity formed around the tank body 1;
[0079] A support plate 2 is sealed and arranged in the accommodating cavity, and a liquid collecting cavity is formed with the tank body 1 below the support plate 2; a purge gas adsorption cavity is formed with the tank body 1 above the support plate 2; the support plate 2 is provided with an opening, and the aperture of the opening is 10 mm;
[0080] The sponge 3 disposed on the support plate 2 is used to contact with the purge gas and condense the condensable gas in the purge gas into liquid droplets;
[0081] A purge gas inlet pipeline 4 and a purge gas outlet pipeline 5 are provided through the tank body 1, wherein the port of the purge gas inlet pipeline 4 is provided below the support plate 2, and the port of the purge gas outlet pipeline 5 is provided above the sponge 3;
[0082] A drain valve 6 is provided at the bottom of the tank body 1 for discharging the collected liquid droplets.
[0083] In the following examples, the vertical burning test grade is tested according to the UL94 flame retardant test method.
[0084] In the following test example, the saturated oil phase adsorption amount and the saturated oil phase adsorption amount after 30 cycles are tested using the following steps: weigh the mass of the sponge to be tested m1, place it in a beaker filled with 200mL toluene, weigh the mass of the sponge after adsorption saturation m2, and the saturated oil phase adsorption amount (Ф): Ф=m1 / m 2。 The test of the saturated oil phase adsorption after 30 cycles was first performed by saturating the sponge with toluene and mechanically squeezing it until no oil phase dripped naturally. This was repeated 30 times, and the subsequent test steps were consistent with the saturated oil phase adsorption.
[0085] In the following embodiments, the water contact angle parameters were measured using the EASY DROP contact angle tester from KRUSS, Germany, with a measurement range of 1-180° and a resolution of ±0.1°. A static contact angle measurement mode was used, and a water droplet or white oil droplet with a fixed volume of 2 μL was dropped on the sponge each time. The calculated initial contact angle was taken as the contact angle measurement value of the sponge surface. Six parallel measurements were performed to calculate the average value.
[0086] In the following examples, the following method is used to test the oil and gas adsorption rate of the purge gas: the test temperature (T) is set to 35°C, and the PX device closed sampler is used as an example. After the sampling is completed, the sampled gas fills the pipeline of the same length. Nitrogen is used as the purge gas for purging, and the cumulative purge is n times. The total mass of the condensable gas of the sampled gas is (0.05*n)g, and the weight increase m of the purge gas adsorption tank is recorded.
[0087] Oil and gas adsorption rate (η): η = m / (0.05*n).
[0088] In the following examples, the porous melamine-formaldehyde sponge matrix (Xuxian Industrial) had a porosity of 95% and an average pore size of 100 μm;
[0089] The porous melamine-formaldehyde sponge matrix (Beiyou Building Materials) has a porosity of 96% and an average pore size of 250 μm.
[0090] Preparation Example 1
[0091] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical) and 1 g of hexamethylenetetramine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.
[0092] (2) A 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial) was measured and the above solution was dispersed into the sponge by extrusion dispersion so that the curing agent solution evenly infiltrated the sponge. The extruded sponge was placed in a vacuum oven at 180°C and 3 kPa for curing for 20 min to obtain an oil-absorbing sponge S1.
[0093] In the oil-absorbing sponge S1, the mass of phenolic resin accounts for 2% of the total mass of the oil-absorbing sponge; the average pore size of the oil-absorbing sponge S1 is 100 μm, the porosity is 95%, the open porosity is 98%, the vertical combustion grade is V-0, the contact angle to white oil is 0°, and the contact angle to water is 152.3°; the saturated oil phase adsorption amount is 40 g / g; the saturated oil phase adsorption amount after 30 cycles is 38 g / g.
[0094] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0095] Among them, the SEM image of the oil absorbing sponge S1 is as follows Figure 2 As shown, compared with the melamine-formaldehyde sponge matrix (SEM image as Figure 4 ), the porous skeleton size of the oil-absorbing sponge is slightly larger than that before modification, indicating that the phenolic resin is uniformly solidified on the surface of the porous melamine-formaldehyde sponge matrix skeleton and has through holes, which makes the oil-absorbing sponge highly selective for oil products in oily wastewater and has a large adsorption capacity for oil products.
[0096] Figure 3 The SEM image of the oil-absorbing sponge S1 after 30 cycles. Figure 2 Compared with the above, there is basically no change, so the adsorption capacity of the oil-absorbing sponge has basically not declined when it is recycled 30 times.
[0097] Preparation Example 2
[0098] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical), 0.3 g of hexamethylenetetramine and 0.2 g of m-xylylenediamine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.
[0099] (2) Weigh a 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial), and disperse the above solution into the sponge by extrusion dispersion so that the curing agent solution evenly infiltrates the sponge. Place the sponge after extrusion in a 140° C. vacuum oven for curing for 100 min to obtain an oil-absorbing sponge S2.
[0100] In the oil-absorbing sponge S2, the mass of phenolic resin accounts for 3% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S2 is 100 μm, the porosity is 95%, and the open porosity is 98%; the vertical combustion grade is V-1, the contact angle to white oil is 0°, and the contact angle to water is 153.2°; the saturated adsorption capacity is 38 g / g; the saturated oil phase adsorption capacity after 30 cycles is 37 g / g.
[0101] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0102] Preparation Example 3
[0103] (1) Weigh 10 g of epoxy resin prepolymer solution (Willigut) and 0.6 g of hexamethylenetetramine and dissolve them in 200 mL of acetone. Stir thoroughly to make the solution clear and transparent.
[0104] (2) Weigh a 200*200*150 mm porous melamine-formaldehyde sponge matrix (Beyou Building Materials), and disperse the above solution into the sponge by spraying so that the curing agent solution evenly infiltrates the sponge. Place the extruded sponge in a vacuum oven at 150°C and 5 kPa for curing for 20 min to obtain an oil-absorbing sponge S3.
[0105] In the oil-absorbing sponge S3, the mass of epoxy resin accounts for 3% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S3 is 250 μm, the porosity is 96%, and the open porosity is 98%; the vertical combustion grade is V-0; the contact angle to white oil is 0°, and the contact angle to water is 151.1°; the saturated adsorption capacity is 40 g / g; the saturated oil phase adsorption capacity after 30 cycles is 35 g / g.
[0106] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0107] Preparation Example 4
[0108] The method of Preparation Example 3 was followed, except that the volume of the porous melamine-formaldehyde sponge matrix was 400*400*150 mm; the other conditions were the same as Preparation Example 3, to obtain oil-absorbing sponge S4.
[0109] In the oil-absorbing sponge S4, the mass of epoxy resin accounts for 0.5% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S4 is 250 μm, the porosity is 92%, and the open porosity is 93%; the vertical combustion grade is V-0; the contact angle to white oil is 0°, and the contact angle to water is 146°; the saturated adsorption capacity is 37 g / g; the saturated oil phase adsorption capacity after 30 cycles is 33 g / g.
[0110] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0111] Preparation Example 5
[0112] The method of Preparation Example 3 was followed, except that 20 g of epoxy resin prepolymer solution (Willigut) and 1.2 g of hexamethylenetetramine were weighed and dissolved in 200 mL of acetone; the other conditions were the same as those of Preparation Example 3 to obtain oil-absorbing sponge S5.
[0113] In the oil-absorbing sponge S5, the mass of epoxy resin accounts for 5% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S5 is 240 μm, the porosity is 87%, and the open porosity is 83%; the vertical combustion grade is V-1; the contact angle to white oil is 0°, and the contact angle to water is 155.4°; the saturated adsorption capacity is 32 g / g; the saturated oil phase adsorption capacity after 30 cycles is 30 g / g.
[0114] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0115] Preparation Example 6
[0116] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical) and 1 g of hexamethylenetetramine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.
[0117] (2) taking a 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial), dispersing the above solution into the sponge by extrusion dispersion, so that the curing agent solution evenly infiltrates the sponge, and curing the sponge after extrusion in a vacuum oven at 110° C. and 3 kPa for 80 min to obtain a sponge containing a gel-state phenolic resin; wherein the gel-state phenolic resin sponge accounts for 1% of the total mass of the porous melamine-formaldehyde sponge matrix;
[0118] (3) The solution of step (1) is dispersed into the sponge containing the gel-like phenolic resin obtained in step (2) by extrusion dispersion, so that the solution evenly infiltrates the sponge. The extruded sponge is placed in a vacuum oven at 180° C. and 3 kPa for curing for 20 min to obtain an oil-absorbing sponge S6.
[0119] The phenolic resin accounts for 2% of the total mass of the oil-absorbing sponge S6; the average pore size of the oil-absorbing sponge is 100 μm, the porosity is 95%, the open porosity is 98%, the vertical combustion grade is V-0, the contact angle to white oil is 0°, and the contact angle to water is 153.8°; the saturated oil phase adsorption amount is 44 g / g; the saturated oil phase adsorption amount after 30 cycles is 43 g / g.
[0120] Preparation Example 7
[0121] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical) and 1 g of hexamethylenetetramine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.
[0122] (2) A 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial) was measured and the above solution was dispersed into the sponge by extrusion dispersion so that the curing agent solution evenly infiltrated the sponge. The sponge after extrusion was placed in a vacuum oven at 110° C. and 3 kPa for curing for 80 min to obtain a sponge containing gel phenolic resin; the pre-cured sponge was then placed in a vacuum oven at 180° C. and 3 kPa for curing for 20 min to obtain an oil-absorbing sponge S7.
[0123] In the oil-absorbing sponge S7, the mass of phenolic resin accounts for 2% of the total mass of the oil-absorbing sponge; the average pore size of the oil-absorbing sponge S8 is 100 μm, the porosity is 95%, the open porosity is 98%, the vertical combustion grade is V-0, the contact angle to white oil is 0°, and the contact angle to water is 152.7°; the saturated oil phase adsorption amount is 41 g / g; the saturated oil phase adsorption amount after 30 cycles is 40 g / g.
[0124] Preparation Example 8
[0125] The method of Preparation Example 1 was followed, except that the impregnation amount of the phenolic resin prepolymer was adjusted so that the mass of the phenolic resin accounted for 7% of the total mass of the oil-absorbing sponge. The remaining conditions were the same as those of Preparation Example 1, to obtain oil-absorbing sponge D1.
[0126] In the oil-absorbing sponge D1, the mass of phenolic resin accounts for 7% of the total mass of the sponge; the average pore size of the oil-absorbing sponge D1 is 230 μm, the porosity is 73%, and the open porosity is 69%; the vertical combustion grade is V-2; the contact angle to white oil is 0°, and the contact angle to water is 158.1°; the saturated adsorption capacity is 27 g / g; the saturated oil phase adsorption capacity after 30 cycles is 20 g / g.
[0127] Figure 5 is the SEM photo of sponge D1. Compared with oil-absorbing sponge S1 ( Figure 2 ), the skeleton and the joints of the sponge are obviously covered with more phenolic resin, which reduces the porosity of the sponge and the corresponding saturated adsorption capacity. In addition, the phenolic resin is unevenly distributed on the surface of the skeleton, which is prone to stress concentration during the cyclic use process, resulting in skeleton collapse. Figure 6 This is a photo of the skeleton of sponge D1 after being recycled 30 times. The stacking density of the skeleton has increased significantly, resulting in a decrease in the saturated adsorption capacity.
[0128] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0129] Preparation Example 9
[0130] The method of Preparation Example 1 is followed, except that in step (2), curing is carried out under normal pressure, specifically: the sponge after extrusion is placed in an oven at 180° C. for curing for 20 minutes, and the other conditions are the same as those of Preparation Example 1, to obtain oil-absorbing sponge D2.
[0131] In the oil-absorbing sponge D2, the mass of phenolic resin accounts for 0.2% of the total mass of the sponge; the average pore size of the oil-absorbing sponge D2 is 250 μm, the porosity is 96%, and the open porosity is 98%; the vertical combustion grade is V-0; the contact angle to white oil is 0°, and the contact angle to water is 133.1°; the saturated adsorption capacity is 30 g / g; the saturated oil phase adsorption capacity after 30 cycles is 20 g / g.
[0132] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0133] Examples 1-7 and Comparative Examples 1-2
[0134] The oil-absorbing sponges prepared in Preparation Examples 1-7 and Preparation Examples 8-9 were respectively filled above the support plate 2, and the filling height was 1 / 2 of the tank height above the support plate 2, and then the purge gas adsorption was performed. The adsorption method was as follows:
[0135] The purge gas is input into the liquid collecting chamber through the purge gas inlet pipeline 4. The purge gas contacts the oil absorbing sponge 3 in the purge gas adsorption chamber through the support plate 2. The condensable gas in the purge gas condenses into liquid droplets, which drop into the liquid collecting chamber under the action of gravity.
[0136] The remaining purge gas is discharged through the purge gas outlet pipeline 5;
[0137] The adsorption temperature was 35 °C and the adsorption pressure was normal pressure;
[0138] The purge gas composition is 85 vol% nitrogen, 10 vol% p-xylene, and 5 vol% toluene.
[0139] Comparative Example 3
[0140] According to the method of Example 3, the filled oil-absorbing sponge is an unmodified porous melamine-formaldehyde sponge matrix (Beyou Building Materials) D3, and the other conditions are the same as Example 3.
[0141] Table 1
[0142]
[0143] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A closed sampling purge gas adsorption tank, characterized in that: The adsorption tank includes: A tank body (1) and a receiving cavity formed around the tank body (1); A support plate (2) is sealed and arranged in the accommodating cavity, wherein the support plate (2) and the tank body (1) form a liquid collecting cavity below; and the support plate (2) and the tank body (1) form a purge gas adsorption cavity above; and the support plate (2) is provided with a gas flow channel; A sponge (3) disposed on the support plate (2) is used to contact the purge gas and condense the condensable gas in the purge gas into liquid droplets; A purge gas inlet pipeline (4) and a purge gas outlet pipeline (5) are provided through the tank body (1), wherein a port of the purge gas inlet pipeline (4) is arranged below the support plate (2), and a port of the purge gas outlet pipeline (5) is arranged above the sponge (3); The sponge (3) comprises an oil-absorbing sponge, which comprises a three-dimensional porous polymer matrix and a thermosetting resin coated on the three-dimensional porous polymer matrix; the saturated adsorption capacity of the oil product by the oil-absorbing sponge is not less than 30 g / g; the saturated adsorption capacity of the oil product by the oil-absorbing sponge is still not less than 30 g / g after 30 cycles of adsorption-desorption.
2. The adsorption tank according to claim 1, wherein: A drain valve (6) is also provided at the bottom of the tank body (1) for discharging the collected liquid droplets; and / or The support plate (2) is provided with an opening, and the diameter of the opening is 5-20 mm.
3. The adsorption tank according to claim 1 or 2, wherein: The mass of the thermosetting resin accounts for 0.5-5% of the total mass of the sponge; preferably 2-3%; and / or The saturated adsorption capacity of the oil-absorbing sponge for oil products is 30-50 g / g; the saturated adsorption capacity of the oil-absorbing sponge for oil products is still 30-50 g / g after being used in a desorption-adsorption cycle for 30 times.
4. The adsorption tank according to claim 1 or 2, wherein: The thermosetting resin is selected from at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, unsaturated polyester resin and silicone resin; preferably selected from at least one of phenolic resin, epoxy resin and silicone resin; and / or The three-dimensional porous polymer matrix is selected from at least one of melamine-formaldehyde sponge, polyurethane sponge and ethylene-vinyl acetate sponge, preferably melamine-formaldehyde sponge.
5. The adsorption tank according to claim 1 or 2, wherein: The pore size of the oil absorbing sponge is 10-500 μm; and / or The porosity of the oil-absorbing sponge is greater than or equal to 60%.
6. The adsorption tank according to claim 1 or 2, wherein: The static plane contact angle of the surface of the oil-absorbing sponge to water in air is greater than 135°; and / or The static contact angle of the oil-absorbing sponge surface to white oil is less than 30°; and / or The UL94 vertical burning test grade of the oil absorbing sponge is above V-2.
7. The adsorption tank according to claim 1 or 2, wherein: The preparation method of the oil absorbing sponge comprises: The solution containing thermosetting resin prepolymer and curing agent is dispersed into a three-dimensional porous polymer matrix, and cured under vacuum conditions to obtain the oil-absorbing sponge; the vacuum conditions include: a pressure of 0-10 kPa.
8. The adsorption tank according to claim 1 or 2, wherein: The preparation method of the oil-absorbing sponge comprises: (1) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into a three-dimensional porous polymer matrix, and pre-curing under a first vacuum condition; (2) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into the product obtained in step (1), and curing the product under a second vacuum condition; The first vacuum condition and the second vacuum condition each include: a pressure of 0-10 kPa; Pre-curing conditions include: temperature of 80-120°C; Curing conditions include: temperature of 140-180°C.
9. A closed sampling purge gas adsorption method, characterized in that: The method includes: The purge gas is input into the liquid collecting chamber through the purge gas inlet pipeline (4), and the purge gas contacts the sponge (3) in the purge gas adsorption chamber through the support plate (2), and the condensable gas in the purge gas condenses into liquid droplets, which drip into the liquid collecting chamber under the action of gravity; The remaining purge gas is discharged through the purge gas outlet pipeline (5).
10. The adsorption method according to claim 9, wherein: The purge gas comes from a PX device, and contains 0-10% toluene, 0-20% p-xylene, and 70-98% nitrogen by volume; and / or Adsorption conditions included: temperature of -20-40°C; and / or The liquid droplets collected in the liquid collecting chamber are discharged through the liquid discharge valve (7).
Citation Information
Patent Citations
BONDING PROCESS USING A SPONGE CARRIER
BE875516A
Superhydrophobic sponge as an efficient oil absorbent material for oil spill cleanup applications
CA2945714A1
Carbon foam biological scaffold as well as preparation method and application thereof
CN101934094A
Oxidation-resistant SiC foam and preparation method thereof
CN107663101A
Preparation method of flexible epoxy resin oil-water separation sponge
CN108786181A
